Scrolling social media: can it trigger intentions to visit man-made tourism destinations? - Nofrizal; Nuradli Ridzwan Shah Bin Mohd Dalib; Arizal N; Aznuriyandi; Afred Suci (Taylor and Francis, 2025)
Indexed Publication (Tier 1)